Business Innovation in Phoenix Dancer Company Semarang through YouTube Channel - Maria Veronika Dhianita Oktavia Indratno (SISFORMA, 2018)
In dynamic technology era, a company should use a new innovation.This innovation can improve the competitive advantage, expand the market reach, and also have a new source income. Phoenix Dancer which is already spend 10 years of operation, should take a new innovation in their company. Their old way through participating in the IKAPESTA exhibition is doesn’t bring a good impact anymore. Phoenix Dancer Semarang need a new way so that they can  improve their competitive advantage, expand the market reach, and also have a new source income, and all that goal can be reach using YouTube Channel. YouTube Channel is suitable for Phoenix Dancer Semarang because they are a services company that provides dancing in their customer wedding, gathering, or birthday. This research also take feasibility analysis to knowing that the innovation is feasible or not. This research is using mix-method, and use YouTube Analytic review data to answer the question research, and also observation and further analysis. The conclusion in this research is through YouTube Channel Phoenix Dancer Semarang can improve their competitive advantage in terms of originality content, but not in communication and creativity. They also succeed expand their market reach, but didn’t succeed in making a new source income from YouTube Partner. The feasibility analysis result tells that this innovation is feasible enough to improve and developed more in terms of financial income and operational activity, but not feasible in making new source income for their company.